Spinal Injury for Rheumatoid Arthritis - Khaydarov Sanjar Nizamitdinovich; Yarmukhamedova Saodat Khabibovna; Khusainova Munira Alisherovna; Ergasheva Ma’mura Tashtemirovna (Miasto Przyszłości, 2023)
Rheumatoid arthritis (RA) is one of the most frequent inflammatory diseases of the joints, leading to permanent disability and early death of patients, and one of the frequent manifestations of RA is spinal damage, which significantly worsens the quality of life of such patients. The aim of the study was to evaluate spinal lesion in patients with different variants of RA and the factors determining it. Material and methods. 131 RA patients aged 18 and over were under observation up to 79 years old (45 years on average), among which there were 18% of men and 82% of women. The duration of the disease was 10 years, the first radiological stage of arthritis was established in 8% of cases of the disease, II — in 38%, III — in 35%, IV — in 19%, seropositivity for rheumatoid factor was noted in 77% of the examined patients, and for the presence of antibodies to citrulline cyclic peptide — in 3/4. Extra-articular (system) the form of the disease occurred in 43% of cases, systemic osteoporosis — in 67%. Results. Spinal damage in the form of osteochondrosis and spondyloarthrosis is observed in 1/2 of the number of RA patients, and it is clinically manifest in 35% of cases, which is directly related to the age of patients, involvement of wrist, elbow, hip and sacroiliac joints in the process, the presence of systemic osteoporosis and tendovaginitis, sensory and motor disorders caused by peripheral neuropathy. The ratio of the frequency of mechanical, disfixation, the dysgemic and inflammatory nature of spinal pain in RA is 1 : 2 : 6 : 14. The radiographs show ossification of the outer layers of the intervertebral discs and the formation of syndesmophytes, as well as spondylodiscitis. The involvement of the arch-process joints is characterized by the indistinctness of the articular surfaces and narrowing of the cracks. Vertebral pathology affects the signs of cardiac pathology (changes in electrical conductivity, chamber size, diastolic function of the left ventricle), autonomic changes and severity of neuropathy, and prognostic The indicators are the levels of rheumatoid factor and C-reactive protein in the blood. Conclusions. Spondylopathy is a frequent manifestation of RA, it is interconnected with many clinical and laboratory signs of the disease. In the future, such patients will benefit from active early detection of spinal pathology for timely rehabilitation measures.